Changes in subfoveal choroidal thickness in myopic children with 0.01% atropine, orthokeratology, or their combination - Hao, Qian; Zhao, Qi (International ophthalmology, 2021)
Purpose To compare the changes in subfoveal choroidal thickness (SFChT) in myopic children treated with 0.01% atropine, orthokeratology (OK), or their combination in myopic children, and to study the connection between increase in SFChT and axial length (AL) elongation. Methods This is a prospective, randomized, controlled study. A total of 67 children were included; 22 patients were randomly assigned to the SA group (patients with spectacles and 0.01% atropine), 24 patients were randomly assigned to the OK group (OK), and 21 patients were randomly assigned to the OKA group (OK and 0.01% atropine). Comprehensive ophthalmologic examinations were performed at baseline, 1 month, 6 months, and 12 months. Results After 1 month, SFChT increased by 5.41 ± 1.65 μm in the SA group, 17.46 ± 2.79 μm in the OK group, and 20.19 ± 2.18 μm in the OKA group ( P = 0.00), whereas AL was not significantly increased. After 12 months, the changes of SFChT were not increased significantly compared with that at 1 month; AL increased by 0.20 ± 0.03 mm in the SA group, 0.28 ± 0.03 mm in the OK group, and 0.14 ± 0.03 mm in the OKA group ( P = 0.00). The change in SFChT at 12 month was negatively correlated with the change in AL at 12 months. Conclusion The control of AL elongation was better in SA group than OK group. The increase in SFChT was best in OKA group, followed by OK group, and the changes were significant after only 1 month. In addition, the increase in SFChT may influence AL elongation and myopia progression.